Dataset for SOU 2023:18 The Wind's Value - Compensation, Incentives and Planning for a Continued Sustainable Wind Power Development - Liljeberg, Ulrika; Schain, Mattias; Forsbacka, Kristina; M 2022:03 Stronger Local Incentives for Wind Power (M 2022:03, Stärkta incitament för utbyggd vindkraft, 2023)
The study is a Governmental Inquiry Commission (SOU). The directives are established in directives 2022:27 and 2022:135, as decided by the Swedish Government. The main task is to develop (1) proposals that strengthen the municipalities' incentives to participate in the expansion of wind power, and (2) systems to compensate those whose surroundings are significantly affected by such expansion. The commission was conducted between April 7, 2022 and April 27th, 2023. The data material consists of the commission report's documentation. This includes, among other things, consequence calculations and data analysis based on the real property register and the database "Vindbrukskollen", surveys from wind power developers, so-called rural development agreements from Sweden's municipalities as well as various authority and research reports.

The data material consists of the commission report's documentation. This includes, among other things, consequence calculations and data analysis based on the real property register and the database "Vindbrukskollen", surveys from wind power developers, so-called rural development agreements from Sweden's municipalities as well as various authority and research reports.

It is not possible to provide access to all parts of the data material as openly accessible data. Please refer to the table of contents and note that some files are only available through the Swedish National Archives.

Utredningen är en statlig offentlig utredning (SOU). Uppdraget framgår av regeringens direktiv 2022:27 och 2022:135. Kärnan i uppdraget är att lämna förslag som stärker kommunernas incitament att medverka till utbyggnad av vindkraft, och på system för att kompensera dem vars omgivning påtagligt påverkas av sådan utbyggnad. Utredningen har bedrivits mellan den 7 april 2022 och den 27 april 2023. Datamaterialet består av betänkandets underlag. Detta inbegriper bland annat konsekvensberäkningar och datakörningar mot fastighetsregistret och databasen Vindbrukskollen, enkätmaterial till vindkraftsprojektörer, insamlade s.k. bygdemedelsavtal från Sveriges kommuner samt diverse myndighets- och forskningsrapporter.

Datasetet består av betänkandets underlag. Detta inbegriper bland annat konsekvensberäkningar och datakörningar mot fastighetsregistret och databasen Vindbrukskollen, enkätmaterial till vindkraftsprojektörer, insamlade s.k. bygdemedelsavtal från Sveriges kommuner samt diverse myndighets- och forskningsrapporter.

Alla delar av materialet kan inte tillgängliggöras som öppet tillgängliga data. Se innehållsförteckningen för detaljer om vad som ingår i detta dataset och vad som endast finns hos Riksarkivet.
Dataset för SOU 2023:18 Värdet av vinden - Kompensation, incitament och planering för en hållbar fortsatt utbyggnad av vindkraften
Keywords: energy; energi; energy policy; energipolitik; WIND FARM; electric power; elkraft; energy production; energiproduktion; renewable energy source; förnyelsebar energikälla; wind power; vindkraft; wind power station; vindkraftsstation; energy infrastructure; energiinfrastruktur; SOU; SOU; Governmental Inquiry Commission; statlig offentlig utredning; Social Sciences; Samhällsvetenskap